Injectable Silk Foams for the Treatment of Cervical Insufficiency. - Fournier, Eric. (2017)
Abstract: Preterm birth is the leading cause of neonatal mortality, resulting in over 4,000 deaths each year. A significant risk factor for preterm birth is cervical insufficiency, the weakening and subsequent deformation of cervical tissue. Cervical insufficiency is both detectable and treatable but current treatments are lacking. The most common approach requires multiple invasive procedures. This work investigates the injection of silk foams, a minimally-invasive method for supporting cervical tissue. Silk offers many advantages for use as a biomaterial including strength, versatility, and biocompatibility. Injectable silk foams will minimize patient discomfort while also providing more targeted and personalized treatment. A battery of mechanical testing was undertaken to determine silk foam response under physiologically relevant loading and environmental conditions. Mechanical testing was paired with analysis of foam morphology and structure that illustrated the effects of injection on pore geometry and size. Biological response to silk foams was evaluated using an in vitro degradation study and subcutaneous in vivo implantation in a mouse model. Results showed that foams exceeded the mechanical requirements for stiffening cervical tissue, although the current injection process limits foam size. Injection was shown to cause measurable but localized foam deformation. This work indicates that silk foams are a feasible treatment option for cervical insufficiency but challenges remain with foam delivery.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Gary Leisk.; Committee: Anil Saigal, Michael House, and David Kaplan.; Keywords: Mechanical engineering, Materials Science, and Biomedical engineering.